OPTIMIZATION OF PHOTOVOLTAIC COOLING SYSTEM PERFORMANCE: A COMPARISON REVIEW OF ACTIVE, PASSIVE AND COMBINED METHODS - Novitasari, Alfiah Jihan; Dionova, Brainvendra Widi; Jaenul, Ariep; Abdullah, Muhammad Irsyad (Transmisi: Jurnal Ilmiah Teknik Elektro, 2025)
Photovoltaic modules play a crucial role in the generation of renewable energy. However, their performance is highly sensitive to temperature changes, as excessive heat can significantly reduce photovoltaic efficiency and electrical output. To counteract this issue, an effective cooling system is essential to maintain the optimal operating temperature of PV modules. Therefore, a cooling system is needed to maintain the optimal temperature and increase the output. This paper compares various cooling approaches categorized into three main types: active, passive, and hybrid (combined) cooling methods. Active cooling methods, such as forced air cooling and water circulation systems, are capable of significantly reducing the temperature of photovoltaics. However, they often require external power sources, which can reduce overall energy efficiency. Passive cooling techniques, including heat sinks, phase change materials (PCMs), and natural convection, offer energy-efficient alternatives that do not require external power, although their cooling capacity may be limited. Hybrid cooling methods, which integrate active and passive elements, have demonstrated superior performance by balancing energy consumption and cooling effectiveness. Effective cooling not only improves performance but also extends the life of the system. Cooling technology should focus on cost-effective, eco-friendly solutions to enhance solar module performance and support efficient renewable energy use.